RATIONALIZATION OF CURVES RESTRUCTURING PLAN AT HIGHER SPEED MOTION OF TRAINS - Rybkin, V. V.; Kurhan, M. B.; Kurhan, D. M.; Kharlan, V. I. (Science and Transport Progress, 2003)
The approach of a reorganization of curves in the plan which is based on minimization of action of a cargo rolling stock for a way and comfortableness of passengers driving at introduction of hight–speed movements is offered.